Ujaran Kebencian dalam Film Crash: Analisis Bentuk dan Fungsi - Salsa Rahmiawati Fadila; Lusi Susilawati (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
The study examines hate speech in the film Crash as a representation of social interaction influenced by stereotypes, prejudice, and power relations among characters. The objective of this research is to identify and analyze the form and pragmatic function of hate speech as manifested in the film’s dialogues. A descriptive qualitative method was employed, with data collected through observation and note-taking techniques. The data consist of selected utterances from character interactions containing elements of hate speech, which were analyzed using a pragmatic approach supported by speech act theory and impoliteness theory. The findings reveal that hate speech is predominantly realized through positive impoliteness strategies, particularly in the form of stereotyping and negative generalizations toward specific social groups. Furthermore, hate speech functions as assertive illocutionary acts through which speakers express and reinforce stereotypical beliefs as if they were socially accepted truths. These results indicate that linguistic expressions in the film not only convey literal meanings but also construct and reflect broader social ideologies and conflicts within a multicultural society.